Evaluation of quality assurance instruments in higher education institutions: A case of Oman - Al-Amri, A. S.; Zubairi , Y. Z.; Jani, R.; Naqvi, S. (South African Journal of Higher Education, 2021)
The use of a variety of instruments for quality assurance, management, and enhancement in higher education is well recognized. This article investigated the instruClose Panelments used by Higher Education Institutions (HEIs) in Oman to measure, control, and manage the quality of their services in alignment with the standards set by Oman Academic Accreditation Authority (OAAA). Quality Assurance Managers (QAMs) from five HEIs were interviewed to identify the instruments used by them to fulfil the requirements of each standard and the way they make use of the data gathered by using these instruments. Findings from the study reveal that questionnaires and meetings are the most common instruments used by these institutions to measure, control and assure the efficacy of their current quality activities. In addition, HEIs use summary statistics to analyse data and then present them in meetings or through reports. On the other hand, it was found that substantial efforts are made to collect data but the efficient usage of data is missing. The QAMs reported a lack of awareness among the staff on the importance of collecting data since the staff members believe that these data are collected for documentation purposes only. This study emphasizes the importance of using the data gathered from different instruments in decision making and enhancing the quality of HEIs.